1996
DOI: 10.1046/j.1475-1313.1996.95001182.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tinted intraocular lens on contrast sensitivity

Abstract: We evaluated contrast sensitivity and glare in 64 pseudophakic eyes. An ultraviolet-absorbing intraocular lens (IOL) was implanted in 32 eyes and a noncyanopsia yellow-tinted IOL was implanted in 32 eyes. The latter lens was designed to effectively absorb light below a wave-length of 500 nm. Contrast sensitivity was measured at a pupil diameter of 3 mm using an artificial pupil. The implanted yellow-tinted IOL showed improved contrast sensitivity in the middle spatial frequencies of 6 and 12 c/deg in photopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…3) have been reported previously. For the previously measured spectral transmittance values, the maximum transmission by the IOLs in the longer visible light range (i.e., [550 nm) sometimes peaked around 90% [7,15], while in the current study the maximum transmission values of all IOLs tested reached 98% or more (Fig. 2).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…3) have been reported previously. For the previously measured spectral transmittance values, the maximum transmission by the IOLs in the longer visible light range (i.e., [550 nm) sometimes peaked around 90% [7,15], while in the current study the maximum transmission values of all IOLs tested reached 98% or more (Fig. 2).…”
Section: Discussionsupporting
confidence: 55%
“…The transmission properties of the colorless UVR-blocking IOLs may not absorb blue light as efficiently compared to aging crystalline lenses and may cause Ham-type retinal phototoxicity [6]. To compensate for this reduced filtration of blue light by the colorless UVR-blocking IOLs, blue-light and UVR-absorbing yellow-tinted polymethylmethacrylate IOLs were introduced in the 1990s [7]. These IOLs are now made of either foldable silicone or soft acrylic material, and there is great interest in using IOLs designed to block blue light [8].…”
Section: Introductionmentioning
confidence: 99%
“…The BFIOL group was noted to have significantly improved contrast sensitivity in the lower to middle frequencies without affecting color vision, and the incidence of photophobia and cyanopsia was less in this group. 61 Niwa et al 62 showed that the BFIOL is associated with better contrast sensitivity in the middle spatial frequencies of 6 and 12 c/deg in photopic and mesopic vision. In addition, the yellow-tinted IOL decreased the effect of central glare on the contrast sensitivity.…”
Section: Influence On Scotopic and Photopic Visionmentioning
confidence: 99%
“…There is evidence for the mild, temporary and more widespread PPP being related to vitreous changes [5], postoperative corneal changes [8]and posterior capsular changes [11]as well as intrinsic characteristics of optics common to many IOL types [5]. Changes in exposure of the retina to different wavelengths of light after cataract extraction may also be involved [14, 15]. Clinical studies suggest that a pseudophakic sensitivity to lower wavelength light might be a factor.…”
Section: Causes Of Pppmentioning
confidence: 99%
“…Clinical studies suggest that a pseudophakic sensitivity to lower wavelength light might be a factor. In an study by Niwa et al [15], patients who were implanted with yellow-tinted IOLs, designed to block light of wavelength less than 500 nm, had significantly fewer problems with glare than those patients with IOLs that absorbed UV light only.…”
Section: Causes Of Pppmentioning
confidence: 99%